2013
DOI: 10.3389/fpsyg.2012.00603
|View full text |Cite
|
Sign up to set email alerts
|

Musical Expertise Modulates Early Processing of Syntactic Violations in Language

Abstract: Syntactic violations in speech and music have been shown to elicit an anterior negativity (AN) as early as 100 ms after violation onset and a posterior positivity that peaks at roughly 600 ms (P600/LPC). The language AN is typically reported as left-lateralized (LAN), whereas the music AN is typically reported as right-lateralized (RAN). However, several lines of evidence suggest syntactic processing of language and music rely on overlapping neural systems. The current study tested the hypothesis that syntacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 70 publications
(163 reference statements)
5
16
1
2
Order By: Relevance
“…It seems likely that the structural reanalysis of less regular events was facilitated by the repeated presentations of these events, thus leading to the LPC decline. This is consistent with studies showing that the amplitude of the LPC is sensitive to the difficulty of integration and the degree of unexpectedness (Fitzroy and Sanders, 2013). Interestingly, this decline was observed even in non-musicians, i.e.…”
Section: Erp Resultssupporting
confidence: 91%
“…It seems likely that the structural reanalysis of less regular events was facilitated by the repeated presentations of these events, thus leading to the LPC decline. This is consistent with studies showing that the amplitude of the LPC is sensitive to the difficulty of integration and the degree of unexpectedness (Fitzroy and Sanders, 2013). Interestingly, this decline was observed even in non-musicians, i.e.…”
Section: Erp Resultssupporting
confidence: 91%
“…Other studies also reported late ERP differences between musicians and non-musicians in oddball paradigms in which participants detected music or speech pitch violation (Besson and Faita, 1995;Granot and Donchin, 2002;Fitzroy and Sanders, 2012;Habibi et al, 2013). Interestingly, previous studies also suggested that the amplitude of the late components can be reduced (more negative) when fewer resources are needed (e.g., Kaan et al, 2000).…”
Section: Influence Of Musical Expertisementioning
confidence: 84%
“…For example, some early studies used event-related potentials (ERPs) and showed that structural violations in music elicit components that resemble those elicited by syntactic violations in language. These include the P600 [151][152][153] (and see Refs. 154 and 155 for original reports of the P600 response to syntactic violations in language) and the early anterior negativity, present more strongly in the right hemisphere (early right anterior negativity (eRAN); 152,156-158 see Refs.…”
Section: Language Versus Music Processingmentioning
confidence: 99%